HALF THE SKY: The Moderating Role of Cultural Collectivism in Job Turnover Among Chinese Female Workers - Chen, Jingqiu (Journal of business ethics, 2016)
The present study examines how collectivism, an important cultural value, plays a moderating role in the association between job attitudes (job satisfaction and organizational commitment) and actual turnover in a sample of 781 Chinese female workers. Results show that collectivism moderates the relationships between job attitude variables and turnover intention. Job satisfaction and organizational commitment are more powerful in predicting turnover intention when levels of collectivism are high rather than low. However, collectivism only moderates the mediation of turnover intention in the relationship between job satisfaction and actual turnover. The study deepens the understanding of the moderating effect of cultural values in organizational behavioral outcomes as Taras et al. (J Appl Psychol 95:405–439, 2010) suggest. Also discussed are the practical implications on how to control the voluntary termination of female laborers who constitute an important part in Chinese manufacturing.